A highly wear-resistant and deformation-resistant PETG composite sheet and preparation method thereof

By introducing hydrogen bonds and amide groups into PETG sheets, forming a cross-linking network, combining nano calcium carbonate and other components, the problem of scrapping caused by deformation of PETG sheets is solved, significantly improving its wear resistance, impact resistance and deformation resistance, and extending the service life.

CN118879042BActive Publication Date: 2025-01-07JIANGSU RUISHENG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411021065.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-07
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

During use, PETG sheets are often scrapped due to raw material deformation, which reduces the service life. The existing enhancement methods have failed to effectively solve the problem of deformation resistance.

Method used

Using high wear and deformation resistance PETG composite sheet formulas, including PET, modified PETG, nano calcium carbonate, toughening agents, antioxidants, lubricants, chain extenders, polyamides and flame retardants, through specific synthesis and Processing technology introduces hydrogen bonds and amide groups to form a crosslinking network to improve deformation resistance.

Benefits of technology

It significantly improves the wear, impact and deformation resistance of the sheet, enhances the thermal stability of the material, and may form dynamic reversible covalent bonds in the crosslinking network, imparting the self-healing performance of the material and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004967284500000101
    Figure BDA0004967284500000101
  • Figure BDA0004967284500000111
    Figure BDA0004967284500000111
  • Figure BDA0004967284500000112
    Figure BDA0004967284500000112
Patent Text Reader

Abstract

The present invention relates to the technical field of plates, and in particular to a highly wear-resistant and deformation-resistant PETG composite plate and a preparation method thereof. The highly wear-resistant and deformation-resistant PETG composite plate of the present invention comprises the following components in parts by weight: 30-50 parts of PET, 10-20 parts of modified PETG, 40-50 parts of nano calcium carbonate, 1-3 parts of toughening agent, 0.5-1 parts of antioxidant, 1-2 parts of lubricant, 1-1.5 parts of chain extender, 0.5-1 parts of polyamide, and 8-12 parts of flame retardant; the highly wear-resistant and deformation-resistant PETG composite plate has good wear resistance, impact resistance, water resistance and tensile properties; and has excellent deformation resistance, which lays a solid foundation for the wide application of PETG plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plates, and in particular to a highly wear-resistant and deformation-resistant PETG composite plate and a preparation method thereof. Background Art

[0002] PETG is a semi-crystalline plastic, which is copolymerized by two main components: terephthalic acid and ethylene glycol. Compared with traditional PET, PETG has higher toughness, transparency, impact resistance and chemical corrosion resistance. It is a transparent or translucent polymer material that can be processed into products of different shapes and sizes by injection molding, blow molding, extrusion and other methods. It can be widely used in consumer goods, medical, construction, decoration, office, packaging and other industries. It has broad development and application prospects. With the continuous changes and expansion of the use environment, higher requirements are put forward for PETG materials.

[0003] At present, the main aspects of PETG reinforcement are inorganic particle reinforcement and polymer blend reinforcement. Patent technical document CN202110073157.7 discloses a weather-resistant and corrosion-resistant PETG sheet and its preparation method. The invention provides a new weather-resistant and corrosion-resistant PETG sheet. The PETG sheet adopts special processes and raw materials, and the obtained PETG sheet has good comprehensive performance, especially excellent weather resistance and corrosion resistance, and has significant advantages. Patent technical document CN201510151877.5 discloses a highly weather-resistant solar cell backplane material and a preparation method. The solar backplane material obtained by the method has good and reliable electrical insulation performance, oxygen barrier performance, water barrier performance, and aging resistance, so that it exhibits excellent weather resistance and can withstand various harsh climatic conditions; the preparation process of the present invention is simple, low cost, and can effectively extend the service life of solar cells. However, in the actual use of the sheet, some raw materials are often deformed, resulting in the scrapping of the sheet, which greatly reduces the service life of the PETG sheet. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a highly wear-resistant and deformation-resistant PETG composite plate and a preparation method thereof, so as to provide a PETG plate with good deformation resistance and wear resistance.

[0005] Based on the above purpose, the present invention provides a highly wear-resistant and deformation-resistant PETG composite plate, comprising the following components in parts by weight: 30-50 parts of PET, 10-20 parts of modified PETG, 40-50 parts of nano calcium carbonate, 1-3 parts of toughening agent, 0.5-1 parts of antioxidant, 1-2 parts of lubricant, 1-1.5 parts of chain extender, 0.5-1 parts of polyamide, and 8-12 parts of flame retardant;

[0006] The preparation steps of the modified PETG are as follows:

[0007] S1: Mix the recycled PET with ethylene glycol, then add potassium carbonate, react at 190-210°C for 2-4 hours, filter, mix the filtered product with methanol, add potassium carbonate, react at 60-70°C for 3-4 hours, filter, centrifuge, and distill to obtain regenerated DMT;

[0008] S2: under a nitrogen atmosphere, deionized water, 6-amino-1-hexanol and dimethyl terephthalate are mixed and reacted at 120-220° C. for 3-5 hours to obtain amide diol;

[0009] S3: Heat and melt 1,4-cyclohexanedimethanol, then mix it with regenerated DMT, ethylene glycol, 2,6-pyridine dimethanol, amide diol and ester exchange catalyst, stir evenly, react at 160-200°C for 2-3h to obtain a prepolymer, then add a polycondensation catalyst and a stabilizer to the reaction system, react at 40-50Pa, 260-290°C for 1-1.5h to obtain modified PETG.

[0010] Preferably, the toughening agent is one of polypropylene grafted maleic anhydride, TPU, TPE, SEBS, EEA, and rubber powder.

[0011] Preferably, the antioxidant is one of antioxidant 1010 and antioxidant 168.

[0012] Preferably, the lubricant is one of OPE wax, amide wax, low molecular weight polyethylene wax and EBS.

[0013] Preferably, the chain extender is one of triglycidyl isocyanurate, pyromellitic dianhydride and epoxy resin.

[0014] Preferably, the particle size of the nano calcium carbonate is 10-100 nm.

[0015] Preferably, the flame retardant is one of magnesium hydroxide, zinc borate and antimony trioxide.

[0016] Preferably, the weight ratio of the recovered PET, ethylene glycol and potassium carbonate in step S1 is 100:200-300:6-8.

[0017] Preferably, in step S1, the weight ratio of the filtered product, methanol and potassium carbonate is 80:20-30:0.2-0.5.

[0018] Preferably, the weight ratio of deionized water, 6-amino-1-hexanol and dimethyl terephthalate in step S2 is 0.1-2:5:6.

[0019] Preferably, the weight ratio of the regenerated DMT, ethylene glycol, 1,4-cyclohexanedimethanol, amide diol, 2,6-pyridine dimethanol, ester exchange catalyst, polycondensation catalyst and stabilizer in step S3 is 200:88-130:36-108:20-41:3.5-10:0.02-0.03:0.04-0.05:0.08-0.1.

[0020] Preferably, the transesterification catalyst in step S3 is zinc acetate.

[0021] Preferably, the polycondensation catalyst in step S3 is antimony trioxide.

[0022] Preferably, the triphenyl phosphate in step S3 is triphenyl phosphate.

[0023] Furthermore, the present invention also provides a method for preparing a highly wear-resistant and deformation-resistant PETG composite sheet, comprising the following steps:

[0024] (1) drying PET and modified PETG in a hot air oven to remove moisture;

[0025] (2) then mixing all the raw materials by weight, putting them into a preheating device, and preheating them at 100-120° C. for 30-60 min;

[0026] (2) introducing the preheated mixed material into a twin-screw extruder, and extruding and cutting the melted mixed material through the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 230-250° C. and the extruder speed is 150-260 r / min.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention introduces a heterocycle into the cross-linked network by adding 6-pyridine dimethanol into the reaction of synthesizing modified PETG, thereby forming hydrogen bonds and π-π interactions, thereby improving the wear resistance, impact resistance and deformation resistance of the final plate.

[0029] (2) The present invention introduces amide groups and a large number of hydrogen bonds into the cross-linked network by adding amide diol into the reaction of synthesizing modified PETG, thereby improving the wear resistance, impact resistance and deformation resistance of the board. In addition, since the amide group has good thermal stability, the board has stronger deformation resistance at high temperature.

[0030] (3) The present invention introduces a large number of hydrogen bonds while also introducing amide groups and heterocycles by adding 6-pyridine dimethanol and amide diol to the reaction of synthesizing modified PETG, thereby improving its wear resistance, impact resistance, and deformation resistance. Most importantly, the two have a certain synergistic effect, which together greatly improves the deformation resistance of the sheet, which is probably caused by the formation of dynamic reversible covalent bonds within the cross-linked network, so that the material has a certain self-healing property. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0032] The nano calcium carbonate used in the examples and comparative examples of the present invention has a particle size of 50 nm and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with the item number C886288.

[0033] Example 1: A highly wear-resistant and deformation-resistant PETG composite sheet, the specific preparation steps are as follows:

[0034] (1) 500 g of recycled PET was mixed with 1000 g of ethylene glycol, and then 30 g of potassium carbonate was added, and the mixture was reacted at 190° C. for 2 h, filtered, 240 g of the filtered product was mixed with 60 g of methanol, 0.6 g of potassium carbonate was added, and the mixture was reacted at 60° C. for 3 h, filtered, centrifuged, and distilled to obtain regenerated DMT;

[0035] (2) Under a nitrogen atmosphere, 0.5 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 120° C. for 3 h to obtain amide diol;

[0036] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 108 g of 1,4-cyclohexanedimethanol was mixed with 200 g of regenerated DMT, 88 g of ethylene glycol, 10 g of 2,6-pyridine dimethanol, 41 g of amide diol and 0.02 g of zinc acetate, stirred evenly, and reacted at 160° C. for 2 h to obtain a prepolymer, and then 0.04 g of antimony trioxide and 0.08 g of triphenyl phosphate were added to the reaction system, and reacted at 40 Pa and 260° C. for 1 h to obtain modified PETG;

[0037] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0038] (5) 30 g of PET, 10 g of modified PETG, 1 g of polypropylene grafted maleic anhydride, 0.5 g of antioxidant 1010, 40 g of nano calcium carbonate, 1 g of EBS, 1 g of pyromellitic dianhydride, 0.5-1 g of polyamide, and 8 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 100 ° C for 30 min;

[0039] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 230° C. and the extruder speed is 150 r / min.

[0040] Example 2: A highly wear-resistant and deformation-resistant PETG composite sheet, the specific preparation steps are as follows:

[0041] (1) 500 g of recycled PET was mixed with 1300 g of ethylene glycol, and then 35 g of potassium carbonate was added, and the mixture was reacted at 200° C. for 3 h, filtered, and 240 g of the filtered product was mixed with 75 g of methanol, and 1.2 g of potassium carbonate was added, and the mixture was reacted at 65° C. for 3 h, filtered, centrifuged, and distilled to obtain regenerated DMT;

[0042] (2) Under a nitrogen atmosphere, 5 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 170° C. for 4 h to obtain amide diol;

[0043] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 72g of 1,4-cyclohexanedimethanol was mixed with 200g of regenerated DMT, 110g of ethylene glycol, 7.5g of 2,6-pyridine dimethanol, 30g of amide diol and 0.03g of zinc acetate, stirred evenly, and reacted at 180°C for 3h to obtain a prepolymer, and then 0.04g of antimony trioxide and 0.09g of triphenyl phosphate were added to the reaction system, and reacted at 45Pa and 275°C for 1.5h to obtain modified PETG;

[0044] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0045] (5) 40 g of PET, 15 g of modified PETG, 2 g of polypropylene grafted maleic anhydride, 0.7 g of antioxidant 1010, 45 g of nano calcium carbonate, 1.5 g of amide wax, 1.3 g of pyromellitic dianhydride, 0.8 g of polyamide, and 10 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 110° C. for 45 min;

[0046] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 240° C. and the extruder speed is 200 r / min.

[0047] Example 3: A highly wear-resistant and deformation-resistant PETG composite sheet, the specific preparation steps are as follows:

[0048] (1) 500 g of recycled PET was mixed with 1400 g of ethylene glycol, followed by the addition of 38 g of potassium carbonate, the reaction was carried out at 210° C. for 3 h, and the mixture was filtered. 240 g of the filtered product was mixed with 80 g of methanol, 1.2 g of potassium carbonate was added, the reaction was carried out at 65° C. for 4 h, and the mixture was filtered, centrifuged, and distilled to obtain regenerated DMT.

[0049] (2) Under a nitrogen atmosphere, 8 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 200° C. for 4 h to obtain amide diol;

[0050] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 69 g of 1,4-cyclohexanedimethanol was mixed with 200 g of regenerated DMT, 120 g of ethylene glycol, 5 g of 2,6-pyridine dimethanol, 25 g of amide diol and 0.03 g of zinc acetate, stirred evenly, and reacted at 200° C. for 3 h to obtain a prepolymer, and then 0.05 g of antimony trioxide and 0.1 g of triphenyl phosphate were added to the reaction system, and reacted at 50 Pa and 270° C. for 1 h to obtain modified PETG;

[0051] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0052] (5) 45 g of PET, 18 g of modified PETG, 3 g of polypropylene grafted maleic anhydride, 10101 g of antioxidant, 45 g of nano calcium carbonate, 2 g of amide wax, 1.4 g of pyromellitic dianhydride, 0.8 g of polyamide, and 11 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 120° C. for 50 min;

[0053] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 250° C. and the extruder speed is 260 r / min.

[0054] Example 4: A highly wear-resistant and deformation-resistant PETG composite sheet, the specific preparation steps are as follows:

[0055] (1) 500 g of recycled PET was mixed with 1000 g of ethylene glycol, followed by the addition of 40 g of potassium carbonate, the reaction was carried out at 210° C. for 4 h, and the mixture was filtered. 240 g of the filtered product was mixed with 90 g of methanol, 1.5 g of potassium carbonate was added, the reaction was carried out at 70° C. for 4 h, and the mixture was filtered, centrifuged, and distilled to obtain regenerated DMT.

[0056] (2) Under a nitrogen atmosphere, 10 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 220° C. for 3-5 h to obtain an amide diol;

[0057] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 36 g of 1,4-cyclohexanedimethanol was mixed with 200 g of regenerated DMT, 130 g of ethylene glycol, 3.5 g of 2,6-pyridine dimethanol, 20 g of amide diol and 0.03 g of zinc acetate, stirred evenly, and reacted at 200° C. for 3 h to obtain a prepolymer, and then 0.05 g of antimony trioxide and 0.1 g of triphenyl phosphate were added to the reaction system, and reacted at 50 Pa and 290° C. for 1.5 h to obtain modified PETG;

[0058] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0059] (5) 50 g of PET, 20 g of modified PETG, 3 g of polypropylene grafted maleic anhydride, 10101 g of antioxidant, 50 g of nano calcium carbonate, 2 g of amide wax, 1.5 g of pyromellitic dianhydride, 1 g of polyamide, and 12 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 120° C. for 60 min;

[0060] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 250° C. and the extruder speed is 260 r / min.

[0061] Comparative Example 1: A PETG composite sheet, the specific preparation steps are as follows:

[0062] (1) 500 g of recycled PET was mixed with 1300 g of ethylene glycol, and then 35 g of potassium carbonate was added, and the mixture was reacted at 200° C. for 3 h, filtered, and 240 g of the filtered product was mixed with 75 g of methanol, and 1.2 g of potassium carbonate was added, and the mixture was reacted at 65° C. for 3 h, filtered, centrifuged, and distilled to obtain regenerated DMT;

[0063] (2) Under a nitrogen atmosphere, 5 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 170° C. for 4 h to obtain amide diol;

[0064] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 72g of 1,4-cyclohexanedimethanol was mixed with 200g of regenerated DMT, 110g of ethylene glycol, 30g of amide diol and 0.03g of zinc acetate, stirred evenly, and reacted at 180°C for 3h to obtain a prepolymer, and then 0.04g of antimony trioxide and 0.09g of triphenyl phosphate were added to the reaction system, and reacted at 45Pa and 275°C for 1.5h to obtain modified PETG;

[0065] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0066] (5) 40 g of PET, 15 g of modified PETG, 2 g of polypropylene grafted maleic anhydride, 0.7 g of antioxidant 1010, 45 g of nano calcium carbonate, 1.5 g of amide wax, 1.3 g of pyromellitic dianhydride, 0.8 g of polyamide, and 10 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 110° C. for 45 min;

[0067] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 240° C. and the extruder speed is 200 r / min.

[0068] Comparative Example 2: A PETG composite sheet, the specific preparation steps are as follows:

[0069] (1) 500 g of recycled PET was mixed with 1300 g of ethylene glycol, and then 35 g of potassium carbonate was added, and the mixture was reacted at 200° C. for 3 h, filtered, and 240 g of the filtered product was mixed with 75 g of methanol, and 1.2 g of potassium carbonate was added, and the mixture was reacted at 65° C. for 3 h, filtered, centrifuged, and distilled to obtain regenerated DMT;

[0070] (2) Under a nitrogen atmosphere, 5 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 170° C. for 4 h to obtain amide diol;

[0071] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 72 g of 1,4-cyclohexanedimethanol was mixed with 200 g of regenerated DMT, 110 g of ethylene glycol, 7.5 g of 2,6-pyridine dimethanol and 0.03 g of zinc acetate, stirred evenly, and reacted at 180° C. for 3 h to obtain a prepolymer, and then 0.04 g of antimony trioxide and 0.09 g of triphenyl phosphate were added to the reaction system, and reacted at 45 Pa and 275° C. for 1.5 h to obtain modified PETG;

[0072] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0073] (5) 40 g of PET, 15 g of modified PETG, 2 g of polypropylene grafted maleic anhydride, 0.7 g of antioxidant 1010, 45 g of nano calcium carbonate, 1.5 g of amide wax, 1.3 g of pyromellitic dianhydride, 0.8 g of polyamide, and 10 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 110° C. for 45 min;

[0074] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 240° C. and the extruder speed is 200 r / min.

[0075] Comparative Example 3: A PETG composite sheet, the specific preparation steps are as follows:

[0076] (1) 500 g of recycled PET was mixed with 1300 g of ethylene glycol, and then 35 g of potassium carbonate was added, and the mixture was reacted at 200° C. for 3 h, filtered, and 240 g of the filtered product was mixed with 75 g of methanol, and 1.2 g of potassium carbonate was added, and the mixture was reacted at 65° C. for 3 h, filtered, centrifuged, and distilled to obtain regenerated DMT;

[0077] (2) Under a nitrogen atmosphere, 5 g of deionized water, 25 g of 6-amino-1-hexanol and 30 g of dimethyl terephthalate were mixed and reacted at 170° C. for 4 h to obtain amide diol;

[0078] (3) 1,4-cyclohexanedimethanol was heated and melted, and then 72g of 1,4-cyclohexanedimethanol was mixed with 200g of regenerated DMT, 110g of ethylene glycol and 0.03g of zinc acetate, stirred evenly, and reacted at 180°C for 3h to obtain a prepolymer, and then 0.04g of antimony trioxide and 0.09g of triphenyl phosphate were added to the reaction system, and reacted at 45Pa and 275°C for 1.5h to obtain modified PETG;

[0079] (4) drying PET and modified PETG in a hot air oven to remove moisture;

[0080] (5) 40 g of PET, 15 g of modified PETG, 2 g of polypropylene grafted maleic anhydride, 0.7 g of antioxidant 1010, 45 g of nano calcium carbonate, 1.5 g of amide wax, 1.3 g of pyromellitic dianhydride, 0.8 g of polyamide, and 10 g of magnesium hydroxide were mixed evenly, put into a preheating device, and preheated at 110° C. for 45 min;

[0081] (6) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 240° C. and the extruder speed is 200 r / min.

[0082] Performance Testing

[0083] Wear resistance test: The caster wear resistance test was performed on the samples obtained in the embodiment according to ISO4918 to observe whether delamination, opening, surface damage, cracking, etc. appeared on the surface of the material after 35,000 revolutions. The test results are shown in Table 1.

[0084] Impact resistance test: The samples obtained in the example were tested according to EN 13329:2006, using a large ball to drop from 1800 mm to observe whether there were cracks, delamination, peeling and other damage on the surface;

[0085] Water absorption expansion rate test: The samples obtained in the embodiment were tested according to ISO24336. The test results are shown in Table 1.

[0086] Buckle tensile strength test: The short side of the sample obtained in the embodiment was tested according to ISO 24334. The test results are shown in Table 1.

[0087] Anti-deformation performance test:

[0088] According to GT / B4085-2015, the samples obtained from the embodiment and the comparative example were subjected to 5°C x 2h warping test, 10°C x 2h warping test, 23°C x 2h warping test and 38°C x 2h warping test, respectively. The test results are shown in Table 2.

[0089] Table 1 Example sample performance test results

[0090]

[0091]

[0092] Table 2 Performance test results of embodiments and comparative examples

[0093]

[0094] Data analysis shows that from Tables 1 and 2, Examples 1-4, it can be seen that the highly wear-resistant and deformation-resistant PETG composite sheet of the present invention has good wear resistance, impact resistance, waterproofness and tensile properties. Most importantly, it has excellent deformation resistance at 0-38°C and can be perfectly used in daily life.

[0095] It can be seen from Example 2 and Comparative Example 1 in Table 2 that the addition of 6-pyridine dimethanol into the reaction for synthesizing modified PETG introduces heterocycles into the cross-linked network, forming hydrogen bonds and π-π interactions, thereby improving the deformation properties of the final sheet.

[0096] It can be seen from Example 2 and Comparative Example 2 in Table 2 that by adding amide diol to the reaction participating in the synthesis of PETG, amide groups and a large number of hydrogen bonds are introduced into the cross-linked network, so that the deformation resistance of the board is improved, and because the amide group has good thermal stability, the board has stronger deformation resistance at high temperature.

[0097] It can be seen from Example 2 and Comparative Examples 1, 2, and 3 in Table 2 that the addition of 6-pyridine dimethanol and amide diol to the reaction of synthesizing PETG not only introduces a large number of hydrogen bonds, but also introduces amide groups and heterocycles, thereby improving its deformation resistance. Most importantly, the two have a certain synergistic effect, which together greatly improves the deformation resistance of the sheet, which is probably caused by the formation of dynamic reversible covalent bonds within the cross-linked network, which gives the material a certain self-healing property.

[0098] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0099] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A highly wear-resistant and deformation-resistant PETG composite sheet, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of PET, 10-20 parts of modified PETG, 40-50 parts of nano calcium carbonate, 1-3 parts of toughening agent, 0.5-1 parts of antioxidant, 1-2 parts of lubricant, 1-1.5 parts of chain extender, 0.5-1 parts of polyamide and 8-12 parts of flame retardant; The preparation steps of the modified PETG are as follows: S1: Mix the recycled PET with ethylene glycol, then add potassium carbonate, react at 190-210°C for 2-4 hours, filter, mix the filtered product with methanol, add potassium carbonate, react at 60-70°C for 3-4 hours, filter, centrifuge, and distill to obtain regenerated DMT; S2: Under a nitrogen atmosphere, deionized water, 6-amino-1-hexanol and dimethyl terephthalate are mixed and reacted at 120-220° C. for 3-5 hours to obtain amide diol; S3: 1,4-cyclohexanedimethanol is heated and melted, and then mixed with regenerated DMT, ethylene glycol, 2,6-pyridine dimethanol, amide diol and ester exchange catalyst, stirred evenly, reacted at 160-200°C for 2-3h to obtain a prepolymer, and then a polycondensation catalyst and a stabilizer are added to the reaction system, and reacted at 40-50Pa, 260-290°C for 1-1.5h to obtain modified PETG; The weight ratio of the regenerated DMT, ethylene glycol, 1,4-cyclohexanedimethanol, amide diol, 2,6-pyridine dimethanol, ester exchange catalyst, polycondensation catalyst and stabilizer in step S3 is 200:88-130:36-108:20-41:3.5-10:0.02-0.03:0.04-0.05:0.08-0.

1.

2. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The toughening agent is one of polypropylene grafted maleic anhydride, TPU, TPE, SEBS, EEA, and rubber powder.

3. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010 and antioxidant 168.

4. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The lubricant is one of OPE wax, amide wax, low molecular weight polyethylene wax and EBS.

5. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The chain extender is one of triglycidyl isocyanurate, pyromellitic dianhydride and epoxy resin.

6. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The weight ratio of the recovered PET, ethylene glycol and potassium carbonate in step S1 is 100:200-300:6-8.

7. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The weight ratio of the filtered product, methanol and potassium carbonate in step S1 is 80:20-30:0.2-0.

5.

8. The highly wear-resistant and deformation-resistant PETG composite sheet according to claim 1, characterized in that: The weight ratio of deionized water, 6-amino-1-hexanol and dimethyl terephthalate in step S2 is 0.1-2:5:

6.

9. A method for preparing a highly wear-resistant and deformation-resistant PETG composite sheet according to any one of claims 1 to 8, characterized in that: The steps include: (1) Dry PET and modified PETG in a hot air oven to remove moisture; (2) Then, all the raw materials are mixed by weight, put into a preheating device, and preheated at 100-120°C for 30-60 minutes; (2) The preheated mixed material is introduced into a twin-screw extruder, and the molten mixed material is extruded and cut by the twin-screw extruder to obtain a highly wear-resistant and deformation-resistant PETG composite sheet, wherein the melting temperature is 230-250°C and the extruder speed is 150-260r / min.

Citation Information

Patent Citations

  • A kind of high weather resistance solar battery back plate material and preparation method

    CN104774434B

  • A weather-resistant and corrosion-resistant PETG sheet and its preparation method

    CN112831162B

  • High-barrier bottle-grade polyester and preparation method thereof

    CN112708117A

  • Sustainable polyesters from recycled polyethylene terephthalate

    CN115867593A